2023
DOI: 10.1021/acs.inorgchem.3c00624
|View full text |Cite
|
Sign up to set email alerts
|

A Dicationic fac-Re(bpy)(CO)3Cl for CO2 Electroreduction at a Reduced Overpotential

Abstract: A dicationic Re bipyridine-type complex, fac-Re-(6,6′-(2-((trimethylammonio)-methyl)phenyl)-2,2′-bipyridine )-(CO) 3 Cl hexafluorophosphate (1 2+ ), has been synthesized, and its electrochemical behavior under Ar and CO 2 has been investigated. The presence of pendent tetra-alkylammonium cations induces an anodic shift in the electrocatalytic potential for CO 2 reduction relative to structurally similar model complexes. The electrochemical mechanisms in anhydrous CH 3 CN and in the presence of weak acids (wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…For the complexes (H)­Ru-CH 3 CN 2+ , (CH 3 )­Ru-CH 3 CN 2+ , and (CH 3 O)­Ru-CH 3 CN 2+ , the reversibility of the second reduction depends on the scan rate. At high scan rates, the second reduction is reversible; however, reversibility decreases at slow scan rates due to competitive reactions, such as formation of the hydride via the protonation of the strongly basic reduced complex with the tetrabutylammonium cation of the electrolyte via the Hofmann degradation (see below). , In contrast, both reduction processes for complexes (Cl)­Ru-CH 3 CN 2+ and (CF 3 )­Ru-CH 3 CN 2+ were reversible, indicating that CH 3 CN dissociation and competitive reactions are slower for the electron-poor molecules.…”
Section: Resultsmentioning
confidence: 99%
“…For the complexes (H)­Ru-CH 3 CN 2+ , (CH 3 )­Ru-CH 3 CN 2+ , and (CH 3 O)­Ru-CH 3 CN 2+ , the reversibility of the second reduction depends on the scan rate. At high scan rates, the second reduction is reversible; however, reversibility decreases at slow scan rates due to competitive reactions, such as formation of the hydride via the protonation of the strongly basic reduced complex with the tetrabutylammonium cation of the electrolyte via the Hofmann degradation (see below). , In contrast, both reduction processes for complexes (Cl)­Ru-CH 3 CN 2+ and (CF 3 )­Ru-CH 3 CN 2+ were reversible, indicating that CH 3 CN dissociation and competitive reactions are slower for the electron-poor molecules.…”
Section: Resultsmentioning
confidence: 99%
“… 18 Ertem, Manbeck, and coworkers have shown that even when the trimethylaminium is further separated from the metal center, the impact of the charge has beneficial properties on catalysis. 19 …”
Section: Introductionmentioning
confidence: 99%
“…18 Ertem, Manbeck, and coworkers have shown that even when the trimethylaminium is further separated from the metal center, the impact of the charge has benecial properties on catalysis. 19 To expand the series of accessible non-N methylated cationic bipyridines and azaarenes, we sought a modular and facile preparation for the direct attachment of trimethylaminium functionalities to azaarenes. Using 6-trimethylaminium-2,2 ′bipyridyl 1 as the target molecule, we initially envisioned synthetic access through either methylation of 6-dimethylamino-2,2 ′ -bipyridyl (Scheme 1), 20 or nucleophilic aromatic substitution of 6-halo-2,2 ′ -bipyridyl with trimethylamine (NMe 3 ) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%